2005 5th International Conference on Information Communications &Amp; Signal Processing
DOI: 10.1109/icics.2005.1689100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Data Replication Strategies for Peer-to-Peer Video Streaming

Abstract: Abstract-Current peer-to-peer (P2P) file-sharing systems are mostly optimized for file availability. This paper investigates P2P architecture for video streaming in general, and the performance impact of data redundancy schemes in particular. In particular, this work show that maximizing file availability is not the best strategy for video streaming as another constraint -peers' streaming bandwidth, comes into play. To address this limitation, a request-rate minimization policy is developed and evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Poon et al [12] reformulated the replication problem in terms of minimizing server's workload. Cheng et al [2] proposed and evaluated a heuristic algorithm of lazy replication.…”
Section: Related Workmentioning
confidence: 99%
“…Poon et al [12] reformulated the replication problem in terms of minimizing server's workload. Cheng et al [2] proposed and evaluated a heuristic algorithm of lazy replication.…”
Section: Related Workmentioning
confidence: 99%
“…The goals of a media streaming strategy include minimizing jitter and latency, while maximizing bandwidth utilization and visual quality. It has been shown that maximizing file availability through techniques such as replication is often not the best strategy when constraints such as bandwidth come into play [2]. Thus, popular methodologies for media streaming are usually achieved through direct server-client relationships, or else, by leverage the strengths of P2P transfers in the form of multicast trees.…”
mentioning
confidence: 98%